Home Sweet Home? Macroeconomic Conditions in Home Countries and the Well-Being of Migrants - Alpaslan Akay; Olivier Bargain; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
This paper examines whether the subjective well-being of migrants is responsive to fluctuations in macroeconomic conditions in their country of origin. Using the German Socio-Economic Panel for the years 1984 to 2009 and macroeconomic variables for 24 countries of origin, we exploit country-year variation for identification of the effect and panel data to control for migrants' observed and unobserved characteristics. We find strong (mild) evidence that migrants' well-being responds negatively (positively) to an increase in the GDP (unemployment rate) of their home country. That is, we originally demonstrate that migrants regard home countries as natural comparators and, thereby, suggest an original assessment of the migration's relative deprivation motive. We also show that migrants are positively affected by the performances of the German regions in which they live (a 'signal effect'). We demonstrate that both effects decline with years-since-migration and with the degree of assimilation in Germany, which is consistent with a switch of migrants' reference point from home countries to migration destinations. Results are robust to the inclusion of country-time trends, to control for remittances sent to relatives in home countries and to a correction for selection into return migration. We derive important implications for labor market and migration policies.
Keywords: C90; D63; 330; migrants; well-being; GDP; unemployment; relative concerns/deprivation